Mindful marketing: A marketing strategy for lingkar to support sustainability goals - Sahisnu, Ramya Prajna; Zaim, Ilma Aulia (International Journal of Accounting and Management Information Systems, 2025)
Purpose: This study explores the implementation of mindful marketing as a strategic approach to harmonize business objectives with social and environmental values. It focuses on Du Anyam, an Indonesian social enterprise, to understand how marketing practices grounded in awareness, ethics, and sustainability contribute to building long-term stakeholder relationships. Research methodology: This study used a qualitative single-case approach, collecting primary data from in-depth interviews with internal stakeholders and secondary data from documents and digital platforms, analyzed thematically to explore Du Anyam’s mindful marketing in communication, distribution, and internal practices. Results: The study finds that Du Anyam implements mindful marketing through three main pillars—self-awareness, consumer-awareness, and impact-awareness—reflected in its storytelling, inclusive product design, and mission-aligned decision-making. However, challenges like digital distractions, workload pressure, and consumer price sensitivity hinder consistent mindful practices. Conclusions: Mindful marketing serves as a strategic compass for social enterprises to navigate market complexities while staying true to ethical values. Its effective practice requires organizational commitment, cultural alignment, and ongoing reflection to create shared value with stakeholders. Limitations: This study is limited to a single case within the Indonesian context, which may constrain the generalizability of its findings to other industries or cultural settings. Additionally, the analysis primarily reflects internal stakeholder perspectives and may not fully capture the diversity of consumer behavior. Contribution: This paper contributes to the evolving discourse on ethical and sustainable marketing by offering a contextualized understanding of mindful marketing practices in emerging economies. It also proposes a practical framework for social enterprises seeking to align marketing strategies with their broader purpose.